The phonology of words with monosyllabic stems in Malay - Zaharani Ahmad; Nor Hashimah Jalaluddin (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
It is generally observed that when monosyllabic stems undergo the process of affixation with verbal prefixes /mN-/ and /di-/ in Malay, two phonological alternations surface in the output forms, namely vowel lengthening (i.e. /di-pam/  [dipam] „to pump (passive)‟), and schwa epenthesis (i.e. /mN-pam/  [mpam] „to pump (active)‟). Unlike the later, the former has not been well examined and accounted for in the previous studies, and therefore the analyses missed some important generalizations about the phonology of the so-called monosyllabic stems in Malay. Previous studies suggested that the so-called monosyllabic stems are lexically disyllabic with an initial empty V-slot at the CV tier. This representation is in agreement with the basic prosodic structure of the words in the language which is normally disyllabic. This empty V-slot triggers the application of vowel lengthening and schwa epenthesis rules, and simultaneously blocks the application of visibly active rules such as nasal assimilation, nasal deletion and nasal substitution. However, based on additional data generated from DBP corpus, it is apparent that there are monosyllabic stems that do not undergo schwa epenthesis as predicted by the rule (i.e. /mN-gam/  [mgam] „to glue‟. This demonstrates that the previous analysis is inadequate and over generalized. The present study concurs that the so-called monosyllabic stems are lexically disyllabic but with an initial empty mora. In the process of syllabification, the empty mora in the rhyme can be linked either with a preceding vowel, an epenthetic schwa or a homorganic nasal.